The impact of industrial design on the competitiveness of Polish enterprises - Mamica, Łukasz (Journal of Public Governance, 2012)
Industrial design is an important factor in the competitiveness of enterprises. In countries where the cost of labour is high, it allows enterprises to create added value of their products. Other expected impacts of good quality design are connected with ergonomics, which has a positive influence on the health of population, cultural heritage and environment (products which are easily recyclable). The paper presents the results of a questionnaire conducted in 2009 and 2010 in 280 Polish enterprises and among 2088 customers familiar with their products. The enterprises were very aware of the role of design in their development (76 per cent consider it key or important), and 70 per cent of them declared that investment in design was profitable. About half of the customers said that design was one of the factors influencing their purchase decision. On a five point scale (where 1 is not important at all and 5 is the most important), it received an average mark of 4.31, compared with 4.45 for product quality, which was deemed the most crucial.